Indentifikasi Keterkaitan Lifestyle Dengan Risiko Diabetes Melitus - Irwansyah Irwansyah; Ilcham Syarief Kasim (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Diabetes is still recorded as the cause of death worldwide with a prevalence that is always increasing significantly, which is indicated by (polyphagy), (polydipsia) (polyuria). Destination; know the relationship between lifestyle and the risk of diabetes mellitus. Method; quantitative research with a descriptive correlative design using a cross-sectional study approach. The sampling technique is propulsive sampling according to the criteria determined by the researcher. Result; There are 50 (55%) respondents who have a good lifestyle and 41 (45%) have a bad lifestyle. There are 53 (58%) respondents who are at risk for diabetes mellitus, 38 (42%) respondents are not at risk. Conclusion: there is a relationship between lifestyle and the Risk of Diabetes Mellitus.